Perspektif Islam terhadap Program Bayi Tabung: Etika, Hukum, dan Hak Waris - Ahmad Sofyan Fauzi; Dinda Difia Madina; M. Rosyid Irfan Alfani (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
Fertilization (IVF) program, especially in the context of ethics, law and inheritance rights. By exploring religious texts and the views of ulama, this research discusses ethical considerations related to the use of artificial reproductive technology in Islam as well as legal interpretations related to its implementation. Apart from that, this research also reviews how Islamic inheritance law regulates the position of children born through IVF. The research method used is the qualitative descriptive method which allows researchers to describe phenomena or research topics in depth, without requiring quantitative measurements. The results of this research show that several ulama' consider the IVF program to be controversial because it is considered to violate natural law or Sunnatullah and is associated with the practice of adultery. However, fatwas from the MUI and NU guide the halalness of the IVF procedure by taking into account religious values ​​and the needs of married couples. In Indonesia, the implementation of this program is regulated by Undang-Undang Nomor 36 Tahun 2009 concerning Health and the MUI fatwa which allows the use of sperm and ovum from legal husband and wife couples. The legal status of children resulting from IVF refers to the Civil Code and Law Number 1 of 1974, with legal recognition depending on the use of donor sperm and surrogate mother. Children born through IVF using the husband's sperm are considered legitimate children with inheritance rights, while inheritance laws for children using donor sperm and surrogate mothers require further consideration.